Smoking cessation for secondary prevention of cardiovascular disease (protocol) - Wu, AD; Hartmann-Boyce, J; Lindson, N; Aveyard, P (Wiley, 2021)
This is a protocol for a Cochrane Review (intervention). The objectives are as follows: